Aplicação do Índice de Proteção da Vida Aquática (IVA) ao sistema estuarino da baía de Vitória - Barbosa, Renata Pasini (2010)
Several water quality indexes were developed by researches. An example is the IVA (Index for Protection of Aquatic Life), which allows changes in its methodology, removing or including parameters to adapt it to different types of water bodies. In this study, IVA was employed at Vitória Bay, a peculiar estuarine system that has been studied in several ways. Also, parameters that belong and other that not belong to the conventional IVA were used in a monitoring carried out within a hydrological year. We observed the changes in these parameters and their interactions to discuss and suggest adjustments in the IVA to fit better in the case of Vitória Bay. We carried out the traditional calculation of IVA and an adapted IVA, were heavy metals were removed and ammonia was included as a reference for the nitrogen compounds entering the system. For Ecotoxicological testing it was used the chronic assay with the Skeletonema costatum, a typical specie of the estuarine region. Also, it was suggested a set of complementary parameters, like salinity, conductivity, water temperature, turbidity, alkalinity and microbiological evaluation using Escherichia coli or Enterococci. Observing adapted IVA, in general the media values in each sample point increased, resulting removal of heavy metals and DO levels modification.